Modern Concepts in Penicillium and Aspergillus Classification 1990
DOI: 10.1007/978-1-4899-3579-3_17
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxonomy and Morphology of Aspergillus Fumigatus and Related Taxa

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…A previous recommendation to elevate A. fumigatus var. ellipticus to the species A. neoellipticus based on mitospore ornamentation (Kozakiewicz 1989) was not followed by Frisvad and Samson (Frisvad and Samson 1990) for similar reasons; only one individual of A. fumigatus var. ellipticus was shown to have the unusual ornamentation and the spore morphology of A. fumigatus sensu stricto were found to be extremely variable.…”
Section: Cryptic Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous recommendation to elevate A. fumigatus var. ellipticus to the species A. neoellipticus based on mitospore ornamentation (Kozakiewicz 1989) was not followed by Frisvad and Samson (Frisvad and Samson 1990) for similar reasons; only one individual of A. fumigatus var. ellipticus was shown to have the unusual ornamentation and the spore morphology of A. fumigatus sensu stricto were found to be extremely variable.…”
Section: Cryptic Speciesmentioning
confidence: 99%
“…ellipticus was shown to have the unusual ornamentation and the spore morphology of A. fumigatus sensu stricto were found to be extremely variable. Moreover, Frisvad and Samson (1990) reported that individuals labeled as A. fumigatus var. fumigatus or A. fumigatus var.…”
Section: Cryptic Speciesmentioning
confidence: 99%
“…Aspergillus fumigatus and Neosartorya fischeri are two closely related euascomycete molds (Eurotiomycetes, Pezizomycotina) in the genus Aspergillus, subgenus Fumigati, section Fumigati (12,33,36,42). A. fumigatus is the most common cause of invasive aspergillosis infection in humans (8,22) and is only known to reproduce by asexual means involving the production of masses of mitotic conidiospores.…”
mentioning
confidence: 99%
“…Members of the Aspergillus section Fumigati are distinguished by the profiles of mycotoxins and secondary metabolites that they produce (2) and, in the case of species with known sexual states (genus Neosartorya), the morphology of the ascospores (17). The evolutionary relationship of A. fumigatus to other species from Aspergillus section Fumigati has been investigated using DNA sequence data obtained from the ␤-tubulin gene (3), the hydrophobin gene (3), and the mitochondrial cytochrome b gene (21).…”
mentioning
confidence: 99%
“…The evolutionary relationship of A. fumigatus to other species from Aspergillus section Fumigati has been investigated using DNA sequence data obtained from the ␤-tubulin gene (3), the hydrophobin gene (3), and the mitochondrial cytochrome b gene (21). These analyses have shown that morphological variation in isolates of A. fumigatus is not necessarily accompanied by variation in chemical profiles or DNA sequences (2,21).…”
mentioning
confidence: 99%